“You have an affiliative leadership style. That's going to be a problem for you.”: Feminized orientations to school leadership and navigating the pipeline - Odell, Sarah Margaret (Frontiers in Education, 2023)
All gender identity is socialized, but anything gendered feminine is marginalized. Up to this point, work on gender and education leadership has remained within the bounds of patriarchy, and thus been confined to binary, hierarchical gender definitions. This study pushes past prior work to advance a more complex and messy understanding of how identity impacts aspiring leaders in their careers. The main question for this study is: how does gender identity and gender performance impact the career journeys of aspiring K12 school leaders. Using Carol Gilligan’s Listening Guide Method, this study contains the interviews of 18 aspiring K12 school leaders who are graduates of Education University. This paper focuses on the key finding that relational leadership, which we come to understand as a feminized orientation to leadership, had a significant impact on aspiring leaders career journeys. This feminized way of leading, keeping relationships at the center of how school leaders thought about their roles, created obstacles and barriers for them on their way to leadership and for some subjects, once they became school leaders. This paper focuses on the interviews of four of the subjects: Rachel, Winston, Taylor and Charlie. These interviews are representative of the themes around relational leadership in the study. Rachel is a White, heterosexual woman, who is mid-to-late career. She has struggled to advance into school leadership because she thinks about her colleagues first and the institution second. Winston is a White, heterosexual male who was successful in becoming a school leader but has left education all together. He found that the higher he ascended as a school leader, the more he was forced to sever his relationships with faculty and students. Taylor is gender non-conforming school leader, who keeps relationships central to his leadership, but has questions about how a non-DEIJ focused leadership position will enable him to show up. Finally, Charlie is Black, heterosexual, female school leader who has been able to keep relationships central to her work. All four interviews demonstrate how relational leadership is marginalized, keeping White Patriarchy as the framework to school leadership.